Candida albicans morphotypes from oral cavity in several families (Boletín Micológico, 1998)
A total of 108 individuals belonging to 22 families consisting of 3 to 8 members each were studied in order to detect Candida albicans morphotypes. Yeasts were isolated from the oral cavity of at least one individual per family, with or without teeth.Following Phongpaichit et al. technique, identical or different morphotypes were detected in 7 families. In 10 families, C. albicans was isolated both from the saliva and the removable denture of the same individual. A discontinuous fringe, considered to be a probable virulence factor, was observed in 9 (16,7%) of the C.albicans strains, from people having the complete set of theet, in the saliva of the former and of those using denture. A continuous fringe was observed in 5 (83,3%) of the C. albicans strains isolated from a same sites. Mosphotyping, a simple ans easily executed method which is useful to detect cross-infection, may serve as a "risk indicator" for the occurrence of candidosis.C. albicans was the prevalent species (86,4%) detected in at least 2 members from 14 families.